Sistem Informasi Magang Berbasis Web Framework Bootstrap 5 (Studi Kasus: Program Studi Informatika, Fakultas MIPA, Universitas Udayana) - Rahayuda, I Gede Surya; Watiniasih, Ni Luh; Santiari, Ni Putu Linda (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 12 No 1 (2023): JELIKU Volume 12 No 1, August 2023DO - 10.24843/JLK.2023.v12.i01.p27, 2023)
The purpose of this research is to overcome some of the problems in the apprenticeship process. From the identification results, the feasibility priority assessment using the APKL criteria identified a priority issue that must be resolved immediately, namely that the apprenticeship process has not been optimal. From the issues that have been analyzed using the APKL screening technique, an in-depth analysis is carried out using the fishbone technique. From several root causes, several creative ideas were obtained, and a main idea was concluded in the form of optimizing the apprenticeship process using a web-based information system. The main idea is embodied in five stages of research using the SDLC method. The system is designed using a DFD, and a relational scheme is used to design the database. The website was built using the Bootstrap 5 framework and added a mapping feature using leaflet.js. From the test results using the graph based black box testing method, good results are obtained, and all processes built can run as expected.     Keywords: APKL, fishbone, SDLC, bootstrap, leaflet.js, black box, graph based.